Business plan for a residential real estate project applying techniques and tools for supply management - Sucñier Carrasco, Franklin (2021)
In essence, housing is one of the most important human aspirations, not only the ability to satisfy one of the basic needs of the family in any society, but also the ability to have a home in informal places like our country. Since the construction industry is such an important part of the country's economic system, it is especially important to check the new management systems implemented in major construction industries around the world and produce excellent results. In this article a review of the master's thesis called "Business Plan of the Pachamamita Residential Real Estate Project, Applying Techniques and Tools for Supply Management" is made, as the city of Cusco makes public and private investments, the population changes drastically and income increases, this completes the incorporation to the emerging real estate sector in which the country lives. The city of Cusco in particular represents a good opportunity for real estate companies. In 2015, date of publication of the master's thesis called "Business Plan of the Pachamamita Residential Real Estate Project, Applying Techniques and Tools for Supply Management" the conditions due to the situation of those years favored and encouraged the real estate offer to be consolidate due to an increase in the demand for low-cost housing units, accessible for socioeconomic level C.